2014
DOI: 10.1111/cod.12275
|View full text |Cite
|
Sign up to set email alerts
|

Failure of total hip implants: metals and metal release in 52 cases

Abstract: We found that cobalt and nickel were released from some failed total hip arthroplasties, and corrosion was frequently observed. Metal ions and particles corroded from metal-on-polyethylene may play a role in the complex aetiopathology of implant failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 27 publications
(33 reference statements)
0
10
0
2
Order By: Relevance
“…About 10% of these, however, will fail, due to infection, mechanical issues, and immune mediated responses to the implant [ 5 ]. All metal implants undergo corrosion in synovial fluid, and release metal ions that can act as haptens to activate the immune system [ 6 ]. As the number of arthroplasties increases worldwide, the incidence of implant failure caused by Ni 2+ hypersensitivity reactions will grow concomitantly.…”
Section: Introductionmentioning
confidence: 99%
“…About 10% of these, however, will fail, due to infection, mechanical issues, and immune mediated responses to the implant [ 5 ]. All metal implants undergo corrosion in synovial fluid, and release metal ions that can act as haptens to activate the immune system [ 6 ]. As the number of arthroplasties increases worldwide, the incidence of implant failure caused by Ni 2+ hypersensitivity reactions will grow concomitantly.…”
Section: Introductionmentioning
confidence: 99%
“…Use of the DPC test for screening purposes resulted in the identification of chromium(VI) release from leather, screws, and earrings. In a former study, we screened 63 alloy parts from 52 failed hip implant patients, and found no positive test reactions with the DPC test . The high rate of positive findings when leather articles were screened was unexpected, but the DPC test appeared to reliably detect chromium(VI) release from leather.…”
Section: Discussionmentioning
confidence: 99%
“…Todas as propostas realizadas até o momento, em maior ou menor quantidade apresentaram falhas. Estudos relatam casos de falhas em implantes fabricados na liga Protasul liga (Co-Cr-Mo) (Martens et al, 1974;Pazzaglia et al, 1988); vitallium (liga Co-Cr-Mo) (Pizzoferrato et al, 1988); aço inoxidável 316L (Godec, 2011;Jakobsen et al, 2014;Kiani Khouzani et al, 2018;Maheshwari et al, 2012;Pazzaglia et al, 1988); aço inoxidável ASTM F-745 (Griza et al, 2008); aço inoxidável F-183 (Hernandez-Rodriguez et al, 2010); liga de titânio (Ceretti & Falez, 2016;Grupp et al, 2010;Jakobsen et al, 2014;Oshima & Fetto, 2015;Paydar et al, 2007;Pizzoferrato et al, 1988); liga Ti-6Al-4V (Chao & López, 2007;Cicero et al, 2007;Jakobsen et al, 2014;Moretti et al, 2012;Pimenta et al, 2021;Williams & Chawla, 2014); fibra de carbono (Adam et al, 2002).…”
Section: O Implanteunclassified